Brown recluse spider venom: Proteomic analysis and proposal of a putative mechanism of action - Dos Santos, Lucilene D.; Dias, Nathalia B.; Pinto, José Robert O.A.S.; Palma, Mario S. [UNESP] (Bentham Science Publishers, 2009)
Loxosceles intermedia spider venom was subjected to proteomic analysis through a MudPIT shot-gun approach to identify the protein composition. Were identified 39 proteins which seem to responsible by the lesion of different types of tissues, to some physiopathological actions and by the prevention of structural damage to the toxin structures. © 2009 Bentham Science Publishers Ltd.
Keywords: Mass spectrometry; Mechanism of action; MudPIT; Proteomic analysis; Spider venom